Prova Brasil : Building a Framework to Promote Measurable Progress in Learning Outcomes - Parandekar, Suhas; Amorim, Érica; Welsh, Andrea (World Bank, Washington, DC, 2012)
Building on two decades of education reform, Brazil's Ministry of Education (MEC) implemented a key instrument for measuring education quality in 2005, when it first administered Prova Brasil, a nationwide test of proficiency in math and Portuguese for students in grades 4 and 8. Prova Brasil, which will be administered to primary students every three years, is the country's first census-level assessment of student learning, and forms the cornerstone of a drive to improve basic education quality and establish a results framework for measuring learning outcomes. The aim of this study has been to promote discussion rather than to provide definitive solutions. Beyond the limited set of specific practices observed and reported upon in the course of this small study, a wide variety of good practices are being implemented in Brazilian school districts, day after day, as teachers, principals, education officials, and parents each make their indispensable contributions to student learning. The reason one municipality achieves better test scores than another is almost certainly due to a occurrence of good practices and the interaction among them, or to a particular confluence of local characteristics and events whose effects continue to accumulate over time. Therefore, the description of good practices in this brief policy note can not be taken as the single best recipe for achieving good test results. Quite to the contrary, it is the aim of this study to demonstrate that there are many possible routes to success.